A Geografia dos lugares e das paisagens na perspectiva das experiências e sentimentos no percurso do romance "No caminho de Swann" de Marcel Proust - Domingos, Edson Lopes (2024)
The search is found in between at the debates and dialogues with the Geography and the Literature refunded by place and landscape through novel writing, which become fundamental in our reflections. In the novel “There sides of Swann” by Marcel Proust, we presente the names Charles de Swann and Odette. The places, such as Balbec on the beach and Combray, a small town are places from the narrator´s childhood. Our theorical structural is based on Cultural Geography, which occupy your with diferente aspects of culture in the analisis of socio-spatial phenomena. We take in an depth dialogue trough the marks left by geographers such as Dardel (2015) reffering to lived espace, and Brousseau (1996). When rescue the reading of places and landscapes mobilized by reflections on the writing of literary autors. In the research, a set of experiences and feelings lived by the characters were collected in a qualitative way, we limited our studies Only in the first volume in the face at the trajectory how the characters perceived the landscape and the place, in order to be contributory to understanding how Society creates forms of organizing geographic space. Thus, the literary text becomes an object of analisis with the material scope, in addition to constituting inherent to internal and external aspects in the understanding of concepts fundamental concepts in Geography that contribute to Geographic Knowledge. Underlying this, it´s presente in the section to bring one for qualitative analysis due to the scientific contente required by the reader, by bringing delight and a way of doing Science.